On the possibility to restore the climatic signal in the disturbed record of stable water isotope content in the old (0.4–1.2 Ma) Vostok ice (Central Antarctica) - A. A. Ekaykin; V. Ya. Lipenkov; A. N. Veres; A. V. Kozachek; A. A. Skakun (Лëд и снег)
In this work we have presented new detailed (with the resolution of 10 cm) stable water isotope (δD and δ18O) profile measured in the central Antarctic Vostok ice core section that contains old ice with the age from 0.4 to 1.2 million years. To interpret these data we have developed a model of molecular diffusion in ice and determined the value of so-called «diffusion length». We have demonstrated that the climatic signal in this ice interval is disturbed by a combination of two processes, ice layer folding (that is accompanied by layer overturning and mixing) and molecular diffusion. The whole old ice interval can be divided in 5  zones that differ in terms of character and intensity of these two processes. In three of these zones the climatic signal is partly preserved and could be restored to some extent. However, in the most interesting and old zone  5 (0.75–1.2  Ma) the climatic signal is nearly completely erased and could hardly be reconstructed. At the same time, the isotopic records obtained from the Vostok old ice have preserved the information on the mean level of the isotopic content of ice in glacial and interglacial stages. This gives an opportunity to reveal and study long-term climatic trends with typical duration longer than main climatic cycles (40–100 ka).